Data Bank of Assassinations, 1948-1967 - Feierabend, Ivo ([Verlag nicht ermittelbar], 1984)
This study contains data on 409 assassination events that occurred in 84 countries in the period 1948-1967. The data cover plotted, attempted, or actual assassinations of prominent public figures, such as top government officeholders and military figures, leaders of large trade unions or religious movements, and leaders of minority groups. For each event, information is provided on the country, date, and location of occurrence, the issue involved, the identity of the assassin and of the target, such as the type of group to which the assassin belonged and the political and social position of the target, and the outcome of the event.